Sheltering strangers : critical memoirs from hosting Ukrainian refugees - Briggs, Daniel (Bristol : Bristol University Press, 2025)
This book documents the intimate lives of Ukrainians as they fled their homeland in search of a safe and stable place to stay. The critical memoirs follow the lives of 16 Ukrainian families in a small Spanish town near Madrid and the local families that volunteered to host them during a time of limited state support and an absence of a clear EU plan for the refugees. Through first-hand testimonies, social media messages and photographs, the book reveals the scarring realities of the Ukrainians' upheaval, displacement and trauma alongside the well-meaning sacrifices made by the host families which quickly mutate into moralistic and meritocratic expectations of their new guests. In doing so, the book offers a vivid portrayal of how the tensions of war and displacement play out in real life in real time.
Holding out -. Karina and Katya -- Pastures new -- War sirens old -- Anya's crisis -- Notes -- 7 In search of Slava Ukra.ni -- The future for Europe and the refugee influx -- Makeshift saviours -- To open arms and closed opportunities -- Dead ends -- Failed counteroffensive -- Oksana's cause -- Brighter sky, darker city -- Family fulcrum -- Mayoral re-.election and precarious work top-.up -- Alicia's holiday and Alberto's distant memories of the Ukrainians -- Yana's predicament -- Notes -- References -- Index
JSTOR
Keywords: Ukrainians -- Spain -- Madrid; Refugees -- Spain -- Madrid; Ukrainiens -- Espagne -- Madrid; Réfugiés -- Espagne -- Madrid; SOCIAL SCIENCE / Refugees